PENERAPAN EXPERIENTIAL LEARNING DAN DESIGN THINKING BAGI MAHASISWA DALAM PENCIPTAAN PRODUK PHOTOBOOTH EVENT IMLEK HOTEL - Lestari, Dina (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2020)
This research purpose is to determine the impact of experiential learning for Podomoro University Product Design students by using Kolb development theory and design thinking methods. Students are tested for their capability on problem-solving in creating photo booth for several hotels which is Ibis Style and Novotel Mangga 2 Jakarta, Ibis Serpong and Sahid Serpong hotel. This research using qualitative participatory methods and the data was compiled by using observation sheets with de Bono’s six thinking hats methods, booklets, and mock-ups for visual presentation. This research involving 30 students from the first semester which then divided by 10 groups and spread into 4 supporting hotels. Each hotel competes 2 groups to design one chosen location for the photo booth. The chosen design then funded and produce on a real scale 1:1. All the finished photo booth products and then displayed on hotel public areas and presented to the hotel guest for their Chinese new year theme photo backdrop. The conclusion of this project is that experiential learning methods could improve student’s analytical, creative and critical way of thinking. This research expectation is to give real case study and information about the use of the experiential learning models in the product design program through collaboration with industry.